Examining The Politeness Principles in The Oral Tradition of Jawab Dilaman Malay Society in Kemingking Village, Jambi Province - Irma Suryani; Julisah Izar; Rengki Afria (Mudra Jurnal Seni Budaya, 2023)
Pragmatics is a branch of linguistics that examines the external meaning of an utterance that is interpreted by the listener. This study aimed to examine the Politeness Principles in the oral tradition of "jawab dilaman" of the Malay society in Kemingking Village, Jambi Province. Jawab dilaman is one of the oral tradition the Malay society when the groom came and want to sit beside the bride, this tradition uttered the seloko by the customary elder which consists of some proverbs, the proverbs contain some advice that interesting to analyze by using politeness principle.  This study used the descriptive qualitative method. Data collection techniques used recording and interview techniques. The results obtained were seventeen maxims, including two data maxims of wisdom, two data maxims of generosity, four data maxims of praise, one data maxim of humility, one data maxim of sympathy and one maxim of agreement data. Based on the final result, the maxim that appears the most is the maxim of agreement the consensus maxim wants every speaker and interlocutor to maximize agreement between them and minimize disagreement in speech acts.